2023
DOI: 10.1186/s12967-023-04649-8
|View full text |Cite
|
Sign up to set email alerts
|

The important role of miR-1-3p in cancers

Shangming Dai,
Fengjiao Li,
Shuoguo Xu
et al.

Abstract: Cancer is a malignant tumor that seriously threatens human life and health. At present, the main treatment methods include surgical resection, chemotherapy, radiotherapy, and immunotherapy. However, the mechanism of tumor occurrence and development is complex, and it produces resistance to some traditional treatment methods, leading to treatment failure and a high mortality rate for patients. Therefore, exploring the molecular mechanisms of tumor occurrence, development, and drug resistance is a very important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 194 publications
(210 reference statements)
0
1
0
Order By: Relevance
“…MiR-1-3p is encoded by the miR-1-2 gene located on CHR 18q11.2 ( 100 ). Wang et al found that the level of miRNA-1-3p is decreased in CMEC when chronic heart failure occurs ( 101 ).…”
Section: Role Of Mirna In Cmec In Cardiovascular Diseasementioning
confidence: 99%
“…MiR-1-3p is encoded by the miR-1-2 gene located on CHR 18q11.2 ( 100 ). Wang et al found that the level of miRNA-1-3p is decreased in CMEC when chronic heart failure occurs ( 101 ).…”
Section: Role Of Mirna In Cmec In Cardiovascular Diseasementioning
confidence: 99%